A Statistical Primer: Understanding Descriptive and Inferential Statistics - Byrne, Gillian (Evidence Based Library and Information Practice, 2007)
As libraries and librarians move more towards evidence-based decision making, the data being generated in libraries is growing. Understanding the basics of statistical analysis is crucial for evidence-based practice (EBP), in order to correctly design and analyze research as well as to evaluate the research of others. This article covers the fundamentals of descriptive and inferential statistics, from hypothesis construction to sampling to common statistical techniques including chi-square, correlation, and analysis of variance (ANOVA).